Unique and shared roles of the posterior parietal and dorsolateral prefrontal cortex in cognitive functions - Katsuki, Fumi; Constantinidis, Christos (Frontiers in Integrative Neuroscience, 2012)
The dorsolateral prefrontal and posterior parietal cortex are two parts of a broader brain network involved in the control of cognitive functions such as working memory, spatial attention, and decision making. The two areas share many functional properties and exhibit similar patterns of activation during the execution of mental operations. However, neurophysiological experiments in non-human primates have also documented subtle differences, revealing functional specialization within the fronto-parietal network. These differences include the ability of the dorsolateral prefrontal cortex to influence memory performance, attention allocation and motor responses to a greater extent, and to resist interference by distracting stimuli. In recent years, distinct cellular and anatomical differences have been identified, offering insights into how functional specialization is achieved. This article reviews the common functions and functional differences between the dorsolateral prefrontal and posterior parietal cortex, and their underlying mechanisms.